Evaluating the Fishing Boat Assistance Program through the CIPP-SI Framework: Evidence from Gorontalo Regency, Indonesia - Marlian Mohammad; Ansar Ansar; Hasim Hasim; Zuchri Abdusamad (Journal Public Policy, 2026)
This study aims to evaluate the Fishing Boat Assistance Program for fishers in Gorontalo Regency by integrating sustainability into the Context, Input, Process, Product (CIPP) evaluation framework. Previous evaluations of fisheries assistance programs have primarily focused on program outputs and short-term economic impacts, with limited attention to the social, institutional, economic, and environmental sustainability dimensions that determine long-term program effectiveness. This study employed a qualitative case study approach using the CIPP evaluation model. Data were collected through in-depth interviews, field observations, and document analysis involving officials from the Fisheries Office, fisher group leaders, and program beneficiaries. The findings indicate that the program was generally aligned with fishers’ needs, improved access to productive assets, and enhanced fishing productivity, business capacity, and economic independence. However, limited institutional capacity, inadequate post-distribution monitoring, and insufficient mentoring constrained the long-term sustainability of program outcomes. Based on these findings, this study proposes the Context, Input, Process, Product–Sustainability Integration (CIPP-SI) framework, which extends the conventional CIPP model by systematically incorporating sustainability considerations into each evaluation dimension. The proposed framework contributes to the advancement of public policy evaluation by providing a more comprehensive approach to assessing fisheries assistance programs and offers practical guidance for designing more sustainable and effective fisher empowerment policies.